(untitled) - Bowerman, Bruce L. (Australia, 2005)
The book illustrates the vital importance of forecasting and the various statistical techniques that can be used to produce them. With an emphasis on applications, this book provides both the conceptual development and practical motivation that need to effectively implement forecasts
Keywords: Time-series analysis,Forecasting,Phân tích chuỗi thời gian,Dự báo; Statistical methods,Phương pháp thống kê